FEATURES OF WINDFALLS IN BEECH FORESTS OF CARPATHIANS - Olijnyk, V. S.; Blystiv, V. I. (Forestry and Forest Melioration, 2018)
Introduction In this article, we tested the effect of an important climatic factor, viz. wind, on hornbeam-beech forests in the Ukrainian part of Carpathian Mountains. In the mountainous conditions of the Carpathians, extreme meteorological effects often occur, especially strong winds, which results in quite harmful windfall phenomena covering vast areas of forest massifs. The nature of the windfalls is well studied for the central and north-eastern parts of the Carpathians and the Ciscarpathian regions, where the spruce is dominating in plantations. At the same time, the windbreak of the spruce trees is six times higher than that of the beech ones. In view of this, the opinion was formed that for the Carpathian beech forests the problem of windfalls is not relevant, and therefore their quantitative evaluation in the literature is almost absent. The article aims to bring out the mechanism of windfall propagation in the beech forests of Transcarpathia depending on the orographic and forestry conditions of mountain slopes and the meteorological context. Materials and Methods The relation database given by Production Association “Ukrderzhlisproekt” as on 2010 was analyzed. The studied forests are situated in Mukachevo, Svalyava and Volovets districts in the territories of the appropriate state forest enterprises, lying at the altitude from 200 to 1,280 m above sea level. We examined wind-induced damages with regard to such factors as forest types, slope steepness, altitude, exposition, and forest forming species, both native and cultural. Main forestry parameters of the windfall forest areas after the storm on May 15, 2014, are given in this respect. Results At the low hypsometric levels from 150 to 1,000 m above sea level, the volume of damage is 4 to 9 times as small as at the levels of 400 to 1,300 m. The hornbeam, sessile oak and beech are the least exposed to the wind activity. The European spruce is the least resistant tree species. The largest part of the windfalls (55 %) occurs on the slopes of north-western orientation. This situation is very similar to the pattern of distribution of windfalls on the north-eastern megaslope of Carpathians. However, there are differences regarding the influence of the orientation of slopes on the occurrence of the windfalls, namely, in the beech forests of the south-western megaslope, more than third of the damaged area is on the slopes of southern exposure. Quantitative changes of forestry and taxation indicators of the beech forest stands under the influence of partial windfalls are presented. For this kind of windfalls, the wind-throw of the trees depends slightly on the tree size. Conclusions The volume of wood damaged by windfalls in the belt of beech forests is on average 10 times less compared to the spruce forests. With increasing slopes altitude, the wind resistance of beech stands decreases. The number of windfalls increases with increasing hypsometric levels. The hornbeam, sessile oak and beech are the least exposed to the wind activity. The spruce is the least resistant tree species. Over half of windfall areas appear at the altitudes over 700 m above sea level. There are more than third of the damaged area on the slopes of southern exposures in the beech forests of the south-western megaslope. It is advisable to implement a forest protection system against the windfalls from the altitude of 400 m above sea level, and it should be an integral part of forest management from the altitude of 700 m.